The Pivotal Mechanism Revisited: Some Evidence on Group Manipulation - Anita Gantner; Wolfgang Höchtl; Rupert Sausgruber (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
This paper studies the vulnerability of the pivotal mechanism with respect to manipulation by groups. In a lab experiment, groups decide on the implementation of various alternatives, some of which imply opposite interests for the two subgroups. We investigate the occurrence of tacit and explicit collusion by allowing for communication within subgroups in one treatment and prohibiting it in another. Even though all agents' preferences are common knowledge and there exists a simple symmetric collusive strategy for one subgroup, we find little evidence for tacit collusion, not even with increasing experience. Only when explicit communication is allowed, collusion is established, and it becomes even more pronounced over time.
Keywords: D71; D61; C92; 330; Collective Decision Making; Pivotal Mechanism; Collusion; Öffentliches Gut; Allokationseffizienz; Gruppenentscheidung; Public Choice; Theorie